2023
DOI: 10.1007/s44197-023-00086-4
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 Vaccine Acceptance and Hesitancy Among Health Care Workers in Lebanon

Abstract: Background Lebanon endured its worst economic and financial crisis in 2020–2021. To minimize the impact of COVID-19 pandemic, it is important to improve the overall COVID-19 vaccination rate. Given that vaccine hesitancy among health care workers (HCWs) affects the general population’s decision to be vaccinated, our study assessed COVID-19 vaccine acceptance among Lebanon HCWs and identified barriers, demographic differences, and the most trusted sources of COVID-19 information. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
2

Year Published

2023
2023
2025
2025

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 39 publications
2
5
2
Order By: Relevance
“…In addition, the results are lower than those among six LMICs, where over 90% of HCWs had already been vaccinated [ 58 ], lower than 92% of HCWs in another study in Nigeria [ 126 ], and lower than those seen in Central and West Asian countries where over 96% of HCWs had already been vaccinated when the study was conducted [ 59 ]. The rate is also lower than a mean of 80.3% (median 78% and range 30.1%) among HCWs willing to be vaccinated in the study by Solís Arce et al involving 10 LMICs [ 49 ], 85% of HCWs in the survey by Leigh et al across 23 countries [ 57 ], and an acceptance rate of 86.8% among HCWs in Lebanon with 7.3% undecided [ 61 ]. In addition, the rate is lower than the 94.9% acceptance rate among HCWs in Singapore [ 127 ].…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…In addition, the results are lower than those among six LMICs, where over 90% of HCWs had already been vaccinated [ 58 ], lower than 92% of HCWs in another study in Nigeria [ 126 ], and lower than those seen in Central and West Asian countries where over 96% of HCWs had already been vaccinated when the study was conducted [ 59 ]. The rate is also lower than a mean of 80.3% (median 78% and range 30.1%) among HCWs willing to be vaccinated in the study by Solís Arce et al involving 10 LMICs [ 49 ], 85% of HCWs in the survey by Leigh et al across 23 countries [ 57 ], and an acceptance rate of 86.8% among HCWs in Lebanon with 7.3% undecided [ 61 ]. In addition, the rate is lower than the 94.9% acceptance rate among HCWs in Singapore [ 127 ].…”
Section: Discussionmentioning
confidence: 98%
“…High rates of over 96% of fully vaccinated HCWs have been reported among HCWs in Central and West Asia [ 59 ]. High rates of acceptance or actual vaccination have also been reported in South Africa (89% of HCWs vaccinated) [ 60 ], Lebanon (86.8% acceptance among HCWs, with 7.3% undecided) [ 61 ] and Malawi (82.5% of HCWs had received the first dose of the vaccine) [ 62 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Women and married people were more likely to refuse the vaccine [14]. A more recent study among Lebanese health workers found similar results regarding sex and added that those who were older and had never been infected were more likely to accept getting vaccinated [15].…”
Section: Challenges To Achieving Herd Immunitymentioning
confidence: 99%
“…In fact, innovative measures are highly needed for the control of COVID-19 infection due to the unique situations in India [46] and other countries. For example, the children immunization App for vaccination registration in refugees camps [47], genetic screening [48] for predicting subsequent critical conditions, and improving acceptance rate for COVID-19 vaccination [49] among health care workers (HCWs) and the general population. Moreover, there are an urgent need of emotional and psychological support due to increased stress levels [50] among HCWs.…”
Section: Innovation For Challenges Of Public Health and Sustaiable Gr...mentioning
confidence: 99%